Identifikasi Jenis Tanaman Perdu di Wilayah Universitas Islam Al-Azhar Mataram - Vivin Erlita Ardiyanti; Dita Misfa Ariyani; Diana Laela Sari; Aulia Annisa; Rosalina Edy Swandayani (LOMBOK JOURNAL OF SCIENCE, 2023)
Faculty of Mathematics and Natural Science is a faculty in Unizar which applied concept of green environment. This study aims to determine the species Plant Of Shrubs trees in the Garden of the Faculty of Mathematics and Natural Sciences (FMIPA), Al-Azhar Islamic University (Unizar), Mataram, West Nusa Tenggara. Based on the research, 7 species Plant Of Shrubs in FMIPA Garden, Unizar were obtained, namely: Rombusa, Araceae , Saraca Asoka , Jasminum, Hibercus rosa- Sinensis, Bougenvillea glabra, dan Clhotophytum comosum. Keywords: Plants, Shrubs, Stems.